KNOWLEDGE AND AWARENESS ON GENDER DETERMINATION USING SKULL MORPHOMETRICS IN FORENSICS AMONG DENTAL STUDENTS - Kumaran, Kirthick; Santhanam, Archana (International Journal of Psychosocial Rehabilitation, 2020)
INTRODUCTION: Sex determination from skeletons is a step in the analysis of forensic anthropology. The relationship between morphological characteristics and the gender of the skull is of great importance in forensic anthropology. The aim of the present study is to evaluate the knowledge and awareness on skull morphology for gender determination among dental students MATERIALS AND METHODS: A descriptive cross-sectional survey was conducted among undergraduate dental college students aged 18-25 years from March to April 2020 to assess their knowledge and awareness of skull morphology for gender determination in forensic odontology. A total of 100 participants were involved in the study. A self-administered questionnaire of close-ended questions was prepared, and it was distributed among undergraduate dental college students through the online survey “Google Forms.” The responses were collected, tabulated in an Excel sheet, and analyzed using SPSS software. The chi-square test was used to analyze the level of education of students and their knowledge on skull morphology for gender determination in forensic odontology with statistical significance of p< 0.05. RESULTS: 79% of the dental students were aware that remains of a deceased person can be used for forensic identification, and first-year undergraduate dental students. 74% of the study participants were aware that skeleton remains are used for gender determination CONCLUSION: From the present study, it is evident that undergraduate students had very good knowledge of skull morphology for gender determination. Among the undergraduate dental students, first-year students had good knowledge of the importance of skull morphology in gender determination.